Authority in contention - Myers, Daniel J.; Cress, Daniel M. (Research in social movements, conflicts and change ;, 2004)
In recent years, there has been a surge in social movement theorizing known as the contentious politics approach to studying political protest activity. In 2002, a conference sponsored by the Collective Behavior and Social Movements Section of the American Sociological Association was held at the University of Notre Dame to consider, in part, this development in field. But the conference organizers also wanted to consider more broadly what we collectively consider to be social movement research and theorizing. In part, this means moving beyond a state-centered view of contentious politics and toward a more open definition of what might be fruitfully examined by social movement theories - and in turn what might inform those theories even as we use then in more traditional social movement arenas. This volume represents some of the fruits of that conference and includes four sections that defines social movement authorities challenges beyond state targets, expands our notions of what constitutes repression of social movement activity, examines challenges to cultural authorities and processes, and illustrates the broader notions of authority challenge in three case studies of corporate systems. With this volume, "Research in Social Movements, Conflict and Change" celebrates its 25th anniversary and a history of publishing important, leading edge research and theorizing in the areas pf protest, social conflict, and political change.